2011
DOI: 10.1093/humrep/der077
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed spermatogenesis associated with thickened lamina propria of seminiferous tubules is not caused by dedifferentiation of myofibroblasts

Abstract: Data indicate that dedifferentiation of myofibroblasts is not responsible for disturbed spermatogenesis associated with LP alterations. Thus, myofibroblasts, presumably newly developed in part, might contribute to disturbed spermatogenesis as key players during development of fibrotic LP alterations but not by contractile dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 49 publications
3
27
0
Order By: Relevance
“…Recently, Volkmann et al (2011) immunohistochemically explored the peritubular wall of men with disturbed spermatogenesis associated with a thickened lamina propria and reported detectable MYH11, Cal and cGKI, independently of the clinical background, except for some specimen. In these notable cases, the authors blamed methodological problems for scarce and irregular staining patterns around seminiferous tubules, which were observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Volkmann et al (2011) immunohistochemically explored the peritubular wall of men with disturbed spermatogenesis associated with a thickened lamina propria and reported detectable MYH11, Cal and cGKI, independently of the clinical background, except for some specimen. In these notable cases, the authors blamed methodological problems for scarce and irregular staining patterns around seminiferous tubules, which were observed.…”
Section: Discussionmentioning
confidence: 99%
“…In the adult man, besides SM actin (SMA), specific contractile differentiation markers of peritubular cells are expressed by peritubular cells, namely myosin heavy chain (MYH11) and calponin (Cal) (Schell et al, 2010;Volkmann et al, 2011). MYH11 plays a fundamental role in the development of the contractile power in SM cells (SMCs) (Kiehart, 1990;Hathaway et al, 1991;Chacko & Longhurst, 1994) and mutated MYH11 causes an inherited arterial disease in man (Zhu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…According to Saunders (1976), the thickness of the lamina propria in Bos indicus bulls with testicular degeneration can reach 5.8 mm, demonstrating a clear condition of tubular sclerosis. Volkmann et al (2011) found that approximately 90.0% of the seminiferous tubules with thickening of the lamina propria showed defects in the germ cells and suggested that this measure can be used as testicular histopathological marker.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact that all patients had been under cross-sex hormone therapy before sex reassignment surgery, in accordance with the current guidelines (22), histological evaluation yielded highly heterogeneous results between different patients who underwent the same endocrine treatment. The gradual decrease in spermatogenesis is associated with thickening of the lamina propria of the seminiferous tubules (23), an abnormal change of the tissue that is not observed in the target tissue from prepubertal patients. Therefore, testicular tissues with complete spermatogenesis and meiotic arrest were selected for this study.…”
Section: Selection Of Patient Samplesmentioning
confidence: 94%
“…These differences may be due to the fact that the testicular tissues in this study were obtained from patients with gender dysphoria. Before sex reassignment surgery, these men underwent cross-sex hormone therapy, which resulted in a reduced percentage of seminiferous tubules with complete spermatogenesis and the associated fibrotic remodeling of the tubular wall (23). It appears likely that this combination renders the testicular tissue more sensitive to mechanical dissociation.…”
Section: Figurementioning
confidence: 99%